Determination of toluene hydrogenation kinetics with neutron diffraction. Issue 26 (7th April 2016) - Falkowska, Marta; Chansai, Sarayute; Manyar, Haresh G.; Gladden, Lynn F.; Bowron, Daniel T.; Youngs, Tristan G. A.; Hardacre, Christopher
Abstract : Total neutron scattering has been used to follow the hydrogenation of toluene- d 8 to methylcyclohexane- d 14 over 3 wt% platinum supported on highly ordered mesoporous silica (MCM-41) at 298 K and under 150–250 mbar D2 pressure. Abstract : Total neutron scattering has been used to follow the hydrogenation of toluene- d 8 to methylcyclohexane- d 14 over 3 wt% platinum supported on highly ordered mesoporous silica (MCM-41) at 298 K and under 150 mbar D2 pressure. The detailed kinetic information so revealed indicates that liquid reorganisation inside pores is the slowest step of the whole process. Additionally, the results were compared with the reaction performed under 250 mbar D2 pressure as well as with toluene- h 8 hydrogenation using D2 at 150 mbar.